Pre-notifications increase retention in a 17-year follow-up of adolescents born very preterm - Helin Minttu; Karukivi Max; Rautava Päivi; Hirvonen Milka; Huhtala Mira; Setänen Sirkku; PIPARI Study Group (BMC, 2026)
Objective: Retention is essential in follow-up studies to reduce missing data, which can cause bias and limit the generalizability of the results. We investigated whether pre-notification letters would increase the response rates of approval forms and questionnaires and reduce the need for post-notifications in a prospective follow-up study of 17-year-old adolescents.
Study design: and settings This long-term follow-up study included 269 adolescents were randomized (1:1) into a pre-notification group (n = 132) and a no pre-notification group (n = 137). The pre-notification letter was sent prior to the approval form and questionnaires. The outcome measures were the response rates to the approval forms and questionnaires and the rate of post-notifications required.
Results: The adolescents who received the pre-notifications were more likely to return approval forms (n = 88/132, 67%) than the adolescents who did not receive the pre-notifications (n = 79/137, 58%) (OR 1.5, 95% CI 0.9-2.4). The rates of returned questionnaires were higher in the pre-notification group (n = 82/88, 93%) than in the no pre-notification group (n = 68/79, 86%) (OR 2.2, 95% CI 0.8-6.3). The adolescents who did not receive the pre-notifications were more likely to need the post-notifications than the adolescents who received the pre-notifications (OR 3.0, 95% CI 1.4 to 6.5).
Conclusions: Pre-notifications decreased the need for post-notifications and may increase retention in 17-year-old adolescents. Based on our findings, pre-notification letters are recommended in future follow-up studies in adolescents.